UI/UX Design of the Mobile Application 'Kalem' Using the Double Diamond Method - Rembulan Cahyaninghati; R.M Chairil Andri; Nurul Aslamiah Istiqomah (ASIAN PUBLISHER, 2024)
Abstract This research aims to design a user interface (UI) for a mobile application named